Edukasi Stunting Pada Siswa Sekolah Dasar Pulau Kalmas Kabupaten Pangkep - Idris, Idris; Nursiah, Andi; Fatany, Alief Ihram; Kasmiati, Kasmiati; Anurogo, Dito; Arda, Darmi; Anto, Sardi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Stunting is chronic malnutrition that occurs in the womb and during the first two years of a child's life can result in low intelligence and decreased physical capacity which ultimately leads to decreased productivity, slow economic growth, and prolonged poverty. The purpose of Community Service is Nutrition Education to prevent stunted growth from an early age by teaching students about basic healthy living habits and increasing students' knowledge and understanding of the importance of a balanced diet and proper nutrition for their development. The method of implementing this community service activity is through stunting education delivered by the PkM Team through interactive lectures and small group discussions to encourage student participation. The results of the calculation of the data processing that has been collected are known from 31 students who have normal nutritional status 24 people (77.4%), thin 1 person (3.2%), short 6 people (19.3%). The conclusion is that forming nutritionally aware behavior from an early age, which can ultimately help reduce the prevalence of stunting in the area, especially in students at the Pulau Kalmas Elementary School, Pangkep Regency.